On the physical mechanisms governing the cloud lifecycle in the Central Molecular Zone of the Milky Way - Jeffreson, Sarah; Kruijssen, Diederik (Monthly notices of the Royal Astronomical Society, 2018)
ABSTRACT. We apply an analytic theory for environmentally dependent molecular cloud lifetimes to the Central Molecular Zone of the Milky Way. Within this theor